Perlindungan Hukum Terhadap Anak dalam Perceraian Menurut Perspektif Hukum Keluarga Islam - Sebriyani, Yeni (Fakultas Syariah INSURI Ponorogo, 2023)
The purpose of writing this paper is to examine the concept of legal protection of children in divorce according to the perspective of Islamic family law. By using normative law which is classified as literature research through the collection, evaluation, and analysis of library sources such as books, jurnal, and legislation related to the law of how children divorce according to the perspective of Islamic family law. This study aims to understand child custody, the conditions of nanny, as well as the views of various schools in Islam related to this issue. The results of the analysis are used to construct a narrative about the principles of legal protection of children in divorce according to Islamic Family Law and can have policy implications. The result of this work is a) In Islam, children are considered a gift and have a variety of statuses, with special rights that include income and education. The importance of respecting and protecting the rights of children, including children out of wedlock, are core values in Islamic teachings. b) Protection of children's rights in divorce situations, in particular custody, is an important aspect that emphasizes the need to ensure the welfare of the child and the cooperation of parents to protect those rights.